Transmittance Analysis for the Translucent White Porcelain of the Xing Kiln, China. (11th January 2019) - Wang, W. X.; Chen, Y.; Zhang, Z. Z.; Wang, C. S.
Abstract : The Xing kiln, which is located in Xingtai, Hebei Province, is famous for white porcelain production, especially translucent white porcelain. However, the translucency, as the most important characteristic of translucent white porcelain, is rarely mentioned. In this study, eight samples including translucent white porcelain and non‐translucent white porcelain excavated from the Xing kiln are quantitatively analysed by a transmittance tester. The study points out the defects of the previous concept of translucent white porcelain based on light transmittance and proposes a new definition based on translucency. Translucent white porcelain is not deliberately thinned fine white porcelain, but a special kind of fine white porcelain with a body of excellent translucency. Further analysis reveals that all transmittance values of translucent white porcelain are more than 0.01% with a body thickness less than 6 cm, which is higher than that of non‐translucent white porcelain by about one or two orders of magnitude. The absorption coefficient for translucent white porcelain is close to −0.82, while that for non‐translucent white porcelain is much closer to −1.87. This research will serve to further studies on subjects such as the classification, colouring mechanism and firing technology of the translucent white porcelain of the Xing kiln. Moreover, it is expected to set a new stage for discussing the translucency of ancient porcelain.